1.0k views
3 votes
What is the simplified form of each expression? (6 + 3)^2 - 4

User Adrenalin
by
6.4k points

2 Answers

7 votes

Answer:

77

Explanation:

(6 + 3)² is same as (a + b)²

Since (a + b)² = a² + 2ab + b²

Therefore,

(6 + 3)² - 4

= (36 + 36 + 9) - 4

= 81 - 4

= 77

User Aladine
by
5.4k points
5 votes

Hi there! Hopefully this helps!

-------------------------------------------------------------------------------------------------------

Answer:
\boxed{77}

~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~

Since PEMDAS exists, we will do parentheses "(6+3)" first to get 9.

Then we do the exponent which is:


9^(2) = 81.

Then we subtract.

81 - 4 = 77.

~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~

More broken down explanation:


(6+3)^(2) -4

Add 6 and 3 to get 9.


9^(2) - 4
77

Calculate 9 to the power of 2 and get 81.


81-4 =
77

Subtract 4 from 81 to get, you guessed it, 77!

User Jagdeesh Kumar
by
5.0k points